A study of Coeliccia cyanomelas Ris, 1912 (Odonata: Platycnemididiae). Issue 3 (2nd October 2019) - Yu, Xin; Zhang, Min; Ning, Xin
Abstract : Coeliccia cyanomelas is studied based on a large series of specimens from its whole distribution range. Intraspecies variations of color patterns on the thorax are discussed. Coeliccia sexmaculata Wang, 1994, Coeliccia mingxiensis Xu, 2006, and Coeliccia wilsoni Zhang & Huo, 2011 are all assigned as junior synonyms of Coeliccia cyanomelas . One 'variety' from Guizhou is reported and discussed briefly.